A multivariate measure of dispersion and its limiting distribution - Suwanda Idris (Universiti Kebangsaan Malaysia, 2005)
Total Variance (TV) and Generalized Variance (GV) are commonly used as a measure multivariate dispersion. However, these two statistics has some drawbacks. This paper proposes a new measure of multivariate dispersion, named Vectorial Variance (VV) an inner product for set of operators defined on a Hilbert-Smith space. Since, the exact sampling distribution of VV is difficult to find, therefore the asymptotic sampling distribution is obtained.